Study on Pork Characteristics of Chinese uzhishan Mini-Pig - Jun She Sun; Fei Lu (2002)
This research was conducted to evaluate the meat traits of Wuzhishan mini-pigs (WZSP). Young Xiang-pigs (XPs) and adult Beijing Black-pigs (BPs) were used as the control group of young and adult WZSPs respectively. Studies included evaluation of carcass properties, meat sensory character, edible quality and processing performance. The studies show the WZSP is of thin skin, low back-fat, high lean percentage and meat productivity. The results of meat quality analysis indicate the WZSP pork is of fresh meat color, good elasticity, less marbling, rich amino acid especially pre-flavor amino acid and low intra-muscular fat. Meanwhile, WZSP pork presents benign processing performance of low loose water percentage, low drip loss, and eminent bounding water capability.